2016
DOI: 10.1177/0300985816642228
|View full text |Cite
|
Sign up to set email alerts
|

Verminous Arteritis Due to Crassicauda sp. in Cuvier’s Beaked Whales (Ziphius Cavirostris)

Abstract: The vascular system of Cuvier's beaked whales (CBW) (Ziphius cavirostris; family Ziphiidae), an extremely deep, prolonged-diving cetacean, is increasingly receiving anatomic and physiologic study due to possible anthropogenic interactions; however, vascular pathology rarely has been reported in this species. Thirteen CBW stranded in the Canary Islands from June 2008 to June 2014 were autopsied. A careful dissection of the thoracic and abdominal vasculature was performed on these animals. All had moderate to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 36 publications
(60 reference statements)
4
38
0
Order By: Relevance
“…Consensus sequence of 18S rRNA gene obtained from these present samples was similar to the sequence obtained from parasites found in subcutaneous tissues of a pygmy sperm whale (Kogia breviceps) and identified as C. magna (Jabbar et al 2015). Additionally, this sequence was similar to the partial sequence of a worm located in the kidney of a Cuvier's beaked whale (Ziphius cavirostris) (Díaz-Delgado et al 2016). While adults of C. boopis and C. magna are morphologically distinct and found in different body sites, molecular analysis of the 18S rRNA gene seems insufficient for reliable species identification.…”
Section: Discussionsupporting
confidence: 72%
“…Consensus sequence of 18S rRNA gene obtained from these present samples was similar to the sequence obtained from parasites found in subcutaneous tissues of a pygmy sperm whale (Kogia breviceps) and identified as C. magna (Jabbar et al 2015). Additionally, this sequence was similar to the partial sequence of a worm located in the kidney of a Cuvier's beaked whale (Ziphius cavirostris) (Díaz-Delgado et al 2016). While adults of C. boopis and C. magna are morphologically distinct and found in different body sites, molecular analysis of the 18S rRNA gene seems insufficient for reliable species identification.…”
Section: Discussionsupporting
confidence: 72%
“…Predominant gross renal lesions in bowhead whales with mild to severe crassicauda infection include renal arteritis with and without partial lumen occluding thrombi, single to multiple renal granulomas and renal cysts (Stimmelmayr and Rotstein, unpublished data). Such lesions are similar to what has been described for Cuvier beaked whales ( Díaz-Delgado et al, 2016 ) and less similar to what has been reported for fin, humpback, and blue whales ( Lambertsen, 1986 ). Results from analysis of limited serum chemistry for two bowhead whales (NSB-DWM 2016B16 and 2016B22) suggest that renal lesions were unlikely to have impacted renal function.…”
Section: Infectious Diseasessupporting
confidence: 88%
“…46, 126 and 131 Severe arterial and renal crassicaudiasis was diagnosed in five Cuvier’s beaked whales (CBW; Ziphius cavirostris ) (animal no. 92, 118, 180, 167 and 207) [ 22 ]. Severe pterygoid sinusitis by Nasitrema sp.…”
Section: Resultsmentioning
confidence: 99%
“…Severe arterial and renal crassicaudiasis was observed in five CBW in this group [ 22 ]. Crassicauda magna was identified in two of them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation